Grafiek op de Grens NL - B. - Bex, Florent; Heijden, A.F.Th. Van der; Kuypers, Paul; Nissen, Peter; Schoonen, Rob; Verlinden, Jan; de Kuyper, Eric (Breda : Nieuwe Brabantse Kunst Stichting, 1995)
de Bie, Jan ; Ledent, Ingrid ; Brenneker, Josien ; Rooms, Veerle ; Hoorne, Emiel ; Engelsen, Jacomijn den ; Opsomer, Geert ; Waanders, Hans ; Dalessi, Giovanni ; Cane, Francky ; van den Heuvel, Hilde ; van Ojen, Vincent
bibliografie
biografie
Nederlands
boek
Keywords: België; Nederland